The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s11356-018-1533-1
|View full text |Cite
|
Sign up to set email alerts
|

Vermicompost dose and mycorrhization determine the efficiency of copper phytoremediation by Canavalia ensiformis

Abstract: The phytoremediation of copper (Cu)-contaminated sandy soils can be influenced by the addition of vermicompost to the soil and the mycorrhization of plants. The objective of this study was to evaluate the effects of inoculation with the mycorrhizal fungus Rhizophagus clarus and the addition of different doses of bovine manure vermicompost on the phytoremediation of a sandy soil with a high Cu content using Canavalia ensiformis. Soil contaminated with 100 mg kg Cu received five doses of vermicompost and was cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 63 publications
2
3
0
Order By: Relevance
“…Although the application of fertilizers did not interfere with the production of mycorrhizal structures (Table ), it was verified that inoculated plants generally accumulated more biomolecules (Tables and ), in agreement with reports by Loit et al and Santana et al This advantage has been reported in some studies, and it is believed that an increase in the production of signaling molecules, activation of key enzymes of the metabolic pathways, modulation in the gene expression of important enzymes of the anabolic routes, hormonal alterations, and the plant's defense response may be competing for the observed optimization (Tables and ).…”
Section: Resultssupporting
confidence: 89%
“…Although the application of fertilizers did not interfere with the production of mycorrhizal structures (Table ), it was verified that inoculated plants generally accumulated more biomolecules (Tables and ), in agreement with reports by Loit et al and Santana et al This advantage has been reported in some studies, and it is believed that an increase in the production of signaling molecules, activation of key enzymes of the metabolic pathways, modulation in the gene expression of important enzymes of the anabolic routes, hormonal alterations, and the plant's defense response may be competing for the observed optimization (Tables and ).…”
Section: Resultssupporting
confidence: 89%
“…The synergy between vermicompost and mycorhization results in excellent biomass production. This is in agreement with data in literature (Santana et al, 2018, Oliveira et al, 2015, whose results also indicate a significant increase in plant dry biomasses. However, other studies found conflicting results.…”
Section: Discussionsupporting
confidence: 94%
“…We also used sand as substrate, and after 17 days, our results showed that height reached from 11.7 to 17.4 cm. This suggests that other substrates may be used and subsequently evaluated for their contribution to better seedling development of C. ensiformis after germination It is worth mentioning that C. ensiformis is a plant that presents tolerance and growth in different environments, and its phytoremediative capacity for some contaminants has been reported, such as diesel oil (BALLIANA et al, 2017), lead (Pb) (ALMEIDA et al, 2008), copper (Cu) (SANTANA et al, 2018), and cadmium (Cd) (FRANCATO ZANCHETA et al, 2015). This species has also shown efficient phytoremediation of herbicides, including trifloxysulfuron sodium (PIRES et al, 2003), atrazine (ARTHUR et al, 2000), imazethapyr and imazapic (SOUTO et al, 2015).…”
Section: Evaluation Of Post-germination Development Of C Ensiformismentioning
confidence: 99%